Effective Innovation for Competitive Advantage within an Independent Railway Assurance Organisation - Umeh, Chukwuma (2018)
This research document is focused on the topic “Effective Innovation for Competitive Advantage within an Independent Railway Assurance Organisation” and based on a specific study organisation. The organisation is a railway assurance company that specialises in the independent assessment of railway infrastructure and rolling stock against European Union (EU) legislation and UK railway national technical rules. The report investigates how the study organisation applies innovation in the delivery of its services by assessing how the company measures up against the key factors that drive innovation management (strategy, processes, organisation and culture, linkages/networks, and learning). The aim is to use the results to determine where the study organisation falls short, then recommend solutions which can be used to drive growth and attain market dominance. The research study centres on the five key drivers of innovation management (Strategy, Learning, Linkages, Organisation/Culture, and Processes), and was undertaken by way of an innovation audit in two stages: the first stage applied a quantitative data gathering method by using a questionnaire. The method allowed for the gathering of numerical views on the perception of innovation by employees of the study organisation. The second stage applied a qualitative data gathering method by way of face-to-face interviews of a sample of employees. This allowed the employees to clarify and elaborate on why they made their selections on the questionnaires. The results of this research study accentuated several areas where the perception of innovation can be improved within the study organisation. This research report develops proposals for addressing problem areas identified during the data gathering stage.